Hasil Biji dan Kadar Minyak Jarak Kepyar Lokal Beaq Amor (Ricinus communis L.) pada Berbagai Umur Pemangkasan Batang Utama - Santoso, Bambang Budi; Sudika, I Wayan; Jaya, I Komang Damar; Aryana, I Gusti Putu Muliarta (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2014)
ABSTRACTSuccessful castor (Ricinus communis L.) cropping depends on the reliability of production technique. Branching is a useful agronomic trait because infloresence developed at each branch’s terminal. Pruning is considered as an important technique for branching stimulation. This study attempted to elucidate the effect of main stem pruning on the yield of Beaq Amor local variety of castor (Ricinus communis L.) with short cultivation system. The experiment was conducted on dry land area of Amor-Amor, North Lombok, West Nusa Tenggara during February-July 2011 and was arranged in a single-factor randomized complete block design with three replications. The treatments were four types of pruning (i.e. no pruning, main stem pruning at 30 days after planting, 45 days after planting, and 60 days after planting). The results showed that the effect of pruning was significant on dry seed yield and was not significant on kernel oil content. Pruning at 30 days old and 45 days old plant yielded in the highest dry seed weight (374.9-387.8 g tree-1 or 943.0-974.3 kg ha-1) with oil content of 62.2%.Keywords: branching, canopy, dry seed, Ricinus communis L.